2014
DOI: 10.1111/evj.12267_146
|View full text |Cite
|
Sign up to set email alerts
|

The Equine Cervical Spine: Comparing MRI and Contrast‐Enhanced CT Images with Anatomic Slices in the Sagittal, Dorsal and Transverse Plane

Abstract: This publication is a compilation of all Research Abstracts presented at the Ninth International Conference on Equine Exercise Physiology. Unlike previous ICEEP conferences there will not be a conference proceedings of full length manuscripts. These abstracts succinctly summarise a wide array of investigations relevant to the equine athlete, and will be useful to veterinarians and others involved in management of horses used for sport, work and competition. The abstracts encompass the topics of Applied Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…It is unknown whether general anesthesia might be required for surgical debridement of joint pathology and/or fragment removal. Description of the normal and diseased articular process joints is currently limited to anatomic and imaging studies . In some instances, previously described normal anatomic variations were detected and described in this report (eg, synovial folds), but most of the arthroscopic abnormalities found that were thought to be pathological but not clinical were attributed to adult age or iatrogenic damage.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is unknown whether general anesthesia might be required for surgical debridement of joint pathology and/or fragment removal. Description of the normal and diseased articular process joints is currently limited to anatomic and imaging studies . In some instances, previously described normal anatomic variations were detected and described in this report (eg, synovial folds), but most of the arthroscopic abnormalities found that were thought to be pathological but not clinical were attributed to adult age or iatrogenic damage.…”
Section: Discussionmentioning
confidence: 80%
“…Degenerative changes in the caudal cervical vertebrae have been reported at postmortem examination in 50% of mature horses and are commonly implicated in cases of neck pain, lameness, or subsequent spinal cord compression and ataxia . Current diagnostic imaging modalities available to evaluate cervical articular processes include radiography, ultrasonography, scintigraphy, computed tomography (CT), and MRI . Previous publications have expressed the inadequate equipment size of MRI or CT to accommodate the caudal cervical area of adult horses and described a lack of consistent correlation among other diagnostic imaging modalities and clinical signs in pathologies such as OA or cervical stenotic myelopathy …”
Section: Introductionmentioning
confidence: 99%
“…The capabilities of diagnostic imaging techniques were explored by several authors. The locations of clinically important structures, including the facet joints, spinal cord, cervical nerve roots and intervertebral discs, were identified using magnetic resonance imaging and compared with contrast‐enhanced computerised tomography (CT) imaging in one study . The CT images were able to depict all osseous borders, but magnetic resonance images were found to be superior for soft‐tissue structures.…”
Section: The Neck Back and Pelvismentioning
confidence: 99%
“…Patient size in relation to gantry diameter has so far limited the use of MRI for examination of the lower equine cervical spine and published anatomical and pathological studies are mostly cadaver studies . Given the fast development of technology and considering the fact that CT of the cervical spine is currently feasible, MRI of the cervical spine in live horses might not be too far off.…”
Section: Introductionmentioning
confidence: 99%